Development of a Digital Quality Assurance Framework to Support Sustainable Accreditation in the Faculty of Medicine - Astrida N Marpaung; Nurul Sulviani; Febi Putri Lestari Hutasuhut; Irpan Efendi Rambe; Inawaty Inawaty; Naswa Atika Riskian; Rayhan Azizan (Cattleya Darmaya Fortuna, 2026)
This study aims to develop and evaluate a Digital Quality Assurance (DQA) Framework to support continuous accreditation readiness at the Faculty of Medicine, Universitas Imelda Medan (FK UIM). The study employed a mixed-method approach, combining Design Science Research for framework prototyping with a descriptive correlational (cross-sectional) design using questionnaires administered to lecturers and administrative staff involved in quality assurance. The results show that the level of Digital Quality Assurance Framework implementation was predominantly in the moderate category (45.0%), while the level of continuous accreditation readiness was predominantly in the not-ready category (57.5%). The Chi-Square test indicated a significant relationship between framework implementation and accreditation readiness (p = 0.001), with Spearman correlation showing a strong positive relationship (rs = 0.612). The resulting framework prototype consists of five modules: digital document management, performance indicator dashboard, learning outcome monitoring, early-warning, and automated reporting.